Patient-centred and family-centred care of critically ill patients who are potential organ donors: a qualitative study protocol of family member perspectives. Issue 6 (15th June 2020) - Zheng, Katina; Sutherland, Stephanie; Cardinal, Pierre; Meade, Maureen; Landriault, Angele; Vanderspank-Wright, Brandi; Valiani, Sabira; Shemie, Sam; Appleby, Amber; Keenan, Sean; Weiss, Matthew; Werestiuk, Kim; et al.
Abstract : Introduction: In a patient-centred and family-centred approach to organ donation, compassion is paramount. Recent guidelines have called for more research, interventions and approaches aimed at improving and supporting the families of critically ill patients. The objective of this study is to help translate patient-centred and family-centred care into practice in deceased organ donation. Methods and analysis: This will be a national, qualitative study of family members of deceased organ donors in Canada. We will include family members who had been approached regarding an organ donation decision, including those who agreed and declined, at least 2 months and no later than 3 years after the patients' death. Data collection and analysis is ongoing and will continue until September 2020 to include approximately 250 participants. Family members will be identified and recruited from provincial organ donation organisation databases. Four experienced qualitative researchers will conduct telephone interviews in English or French with audio-recording for subsequent transcription. The research team will develop a codebook iteratively through this process using inductive methods, thus generating themes directly from the dataset. Ethics and dissemination: Local research ethics boards (REB) at all participating sites across Canada have approved this protocol. The main REB involved is the Ottawa Health Science Network REB. Data collection began in August 2018. Publication of results is anticipated in 2021. Study findings will help improve healthcare provider competency in caring for potential organ donors and their families and improve organ donation consent rates. Findings will also help with the development of educational materials for a competency-based curriculum for critical care residents.